Investigation of iron-containing powder on coal combustion behavior. Issue 5 (October 2017) - Zou, Chong; Zhao, Junxue
Abstract: Effects of iron-containing powder on coal combustion behavior were investigated using thermogravimetry (TG) and differential scanning calorimetric (DSC) analysis. The results indicated that the presence of hematite, BOF dust, and BOF sludge reduced ignition temperature, speeded up combustion rate, improved burnout behavior and enhanced the heat release rate during the coal combustion process. However, BF dust generally showed a negative effect on coal combustion behavior. Based on the results of kinetic study, XRD, SEM–EDS and nitrogen adsorption analysis, the possible mechanism of intensified or suppressed combustion by these powder was proposed. The catalytic effect of these iron-containing powder on coal combustion is related not only with the constituents but also with the surface morphology and pore structure of these powder. Highlights: Effects of iron-containing powder on coal combustion behavior were investigated using TG DSC analysis. The presence of hematite, BOF dust, and BOF sludge improved the coal combustion. The possible mechanism of intensified combustion by these powder was proposed.